New assessment technologies to evaluate current and intermediate knowledge of learners - Semenycheva, Irina F.; Latysheva, Valentina V.; Sakulyeva, Tatyana N.; Semenova, Larisa V.; Tikhonova, Yuliya A. (Opción, 2020)
Modern education development trends, and the emergence of new modes of study put forward new requirements for testing. The purpose of the research is to scientifically substantiate the application of testing technologies aimed at increasing student motivation to acquire economic competencies. In order to experimentally verify the feasibility of testing technologies as a factor that increases the motivation and success of learners of non-economic specialties, a pedagogical experiment was conducted. It has been established that the maximum effect is achieved through the integrated approach - the use of testing technologies to assess both current and intermediate (final) knowledge of learners.